Produktivitas Ayam Petelur Strain Isa Brown Pada Umur 24 – 28 Minggu - D Sulaiman; N Irwani; K Maghfiroh (Politeknik Negeri Lampung, 2019)
Laying hens are adult hens that are specially kept for their eggs. This chicken has a high egg production capability. The purpose of this thesis is to determine the level of productivity of ISA Brown strain laying hens aged 24-28 weeks, by calculating and comparing ration consumption standards, Hen Day Production (HDP), Feed Conversion Ratio (FCR), and mortality in laying hens CV Bisco Farm Talang Jawa Village, Merbau Mataram District, South Lampung Regency. The method used in the preparation is directly involved in conducting maintenance, discussion, study literature, and direct interviews. Feed consumption is 101 grams/bird /day, daily egg production or Hen Day Production (HDP) averaged 92.77%, the average FCR value was 1.89, and the mortality rate was 0.07%.Â Key words : layer, egg productivity, performance